Jihad dan Thâ’ifah Manshûrah: Basis Syariah Identitas Kelompok Jihadis - Gazi Saloom (AHKAM : Jurnal Ilmu Syariah, 2016)
This study aims to examine how the concept of jihad and Tha’ifah manshurah psychologically and sociologically shape the strong basis of ideology and collective identities in jihadist community in Indonesia. Three former alumni of Afghanistan serve as key informants and three others play as secondary informants who provide the context of strengthening the jihad ideology and the formation of collective identities on the jihadists in Indonesia. In-depth interviews and review of documents, especially literature written directly by key informants, are used as data collection instruments. All the data that have been collected through interviews and review of documents are then analyzed by using the content analysis technique and thematic analysis. The study concludes that the jihad in the sense of fighting is considered as the only tool to fight the jihadist ideology that tends to perceive themselves as the chosen people of God to fight all the life.DOI: 10.15408/ajis.v16i1.2890